Art of the Possible : An Everyday Guide to Politics - Edward Keenan (Toronto, ON, Canada Owlkids Books Inc., 2016)
We all know what a politician looks like, right? They're old people who wear suits and make long, boring speeches full of indecipherable words. Not so fast! As The Art of the Possible explains, everyone is a politician -- even young people who aren't yet eligible to vote. We all have influence over how politics function. But what are politics, and why do we need them? This book answers the universal query in nine short chapters that explain everything from why we form societies and the basic types of governments to the power of public opinion, methods of rhetoric, and the reasons why politicians "lie." Written in an accessible, conversational voice and packed with anecdotes and case studies from across history and around the world, this book helps foster independent thought and curiosity about how a government works -- or doesn't work. Readers will come away equipped with the knowledge they need to understand current events and elections, and maybe even be empowered to civic action themselves. Informational text features: table of contents, chapters, dia...
Keywords: Politics & Government -- Politics & Government; Politics -- Politics